Hospitalized frail elderly patients – atrial fibrillation, anticoagulation and 12 months’ outcomes - Ekerstad N (Dove Medical Press, 2018)
Niklas Ekerstad,1,2 Thomas Karlsson,3 Sara Söderqvist,4 Björn W Karlson4,5 1Department of Cardiology, NU (NÄL-Uddevalla) Hospital Group, Trollhättan-Uddevalla-Vänersborg, Sweden; 2Department of Medical and Health Sciences, Division of Health Care Analysis, Linköping University, Linköping, Sweden; 3Health Metrics Unit, Institution of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden; 4Department of Acute and Internal Medicine, NU (NÄL-Uddevalla) Hospital Group, Trollhättan-Uddevalla-Vänersborg, Sweden; 5Department of Molecular and Clinical Medicine, Institute of Medicine, Sahlgrenska Academy, University of Gothenburg, Gothenburg, Sweden Background and objective: Multiple chronic conditions and recurring acute illness are frequent among elderly people. One such condition is atrial fibrillation (AF), which increases the risk of stroke up to fivefold. The aim of this study was to investigate the prevalence of AF among hospitalized frail elderly patients, their use of anticoagulation and their 12-month outcomes. Patients and methods: This was a clinical observational study of acutely hospitalized frail patients over the age of 75 years. The CHA2DS2-VASc Score was used to evaluate ischemic stroke risk in patients with AF. Clinically relevant outcomes were the composite of ischemic stroke and/or bleeding within 12 months, which was considered as primary in the analysis, ischemic stroke/transient ischemic attack (TIA), mortality, bleeding and hospital care consumption. Student’s t-test, Fisher’s exact test, Mann–Whitney U test and a Cox proportional hazards model were used for the analyses. Results: The prevalence of AF was 47%, and 63% of them were prescribed an anticoagulant. AF patients without anticoagulation were older, more often females, more often in residential care, and they had worse Mini Nutritional Assessment and activities of daily living scores. Of the patients without anticoagulation, 56% had a documented contraindication. In univariate analysis, there were significantly more events among AF patients without anticoagulation regarding the composite outcome of ischemic stroke and/or bleeding (hazard ratio [HR] 3.65, 95% CI = 1.70–7.86; p < 0.001). When adjusting for potential confounders in Cox regression analysis, the difference remained significant (HR 4.54, 95% CI = 1.83–11.25; p = 0.001). Conclusion: The prevalence of AF in a hospitalized frail elderly population was 47%. Of these, 63% were prescribed anticoagulation therapy. Almost half of the patients without stroke prophylaxis had no documented contraindication. At 1 year, there were significantly more events in terms of ischemic stroke and/or bleeding among AF patients without anticoagulation therapy than among those with. Keywords: frail elderly, atrial fibrillation, anticoagulants, outcomes, patient safety